Mitochondrial dysfunction: roles in skeletal muscle atrophy - Xin Chen; Yanan Ji; Ruiqi Liu; Xucheng Zhu; Kexin Wang; Xiaoming Yang; Boya Liu; Zihui Gao; Yan Huang; Yuntian Shen; Hua Liu; Hualin Sun (Journal of Translational Medicine, 2023)
Abstract Mitochondria play important roles in maintaining cellular homeostasis and skeletal muscle health, and damage to mitochondria can lead to a series of pathophysiological changes. Mitochondrial dysfunction can lead to skeletal muscle atrophy, and its molecular mechanism leading to skeletal muscle atrophy is complex. Understanding the pathogenesis of mitochondrial dysfunction is useful for the prevention and treatment of skeletal muscle atrophy, and finding drugs and methods to target and modulate mitochondrial function are urgent tasks in the prevention and treatment of skeletal muscle atrophy. In this review, we first discussed the roles of normal mitochondria in skeletal muscle. Importantly, we described the effect of mitochondrial dysfunction on skeletal muscle atrophy and the molecular mechanisms involved. Furthermore, the regulatory roles of different signaling pathways (AMPK-SIRT1-PGC-1α, IGF-1-PI3K-Akt-mTOR, FoxOs, JAK-STAT3, TGF-β-Smad2/3 and NF-κB pathways, etc.) and the roles of mitochondrial factors were investigated in mitochondrial dysfunction. Next, we analyzed the manifestations of mitochondrial dysfunction in muscle atrophy caused by different diseases. Finally, we summarized the preventive and therapeutic effects of targeted regulation of mitochondrial function on skeletal muscle atrophy, including drug therapy, exercise and diet, gene therapy, stem cell therapy and physical therapy. This review is of great significance for the holistic understanding of the important role of mitochondria in skeletal muscle, which is helpful for researchers to further understanding the molecular regulatory mechanism of skeletal muscle atrophy, and has an important inspiring role for the development of therapeutic strategies for muscle atrophy targeting mitochondria in the future.